2071. Evaluation of BD Phoenix™ CPO Detect Assay for Detection of Carbapenemase Producing Organisms in Clinical Samples in Singapore. (26th November 2018) - De, Partha P; Ng, Esme; Pin, Tzer; Lin, Raymond; Hart, Tim
Abstract: Background: Rapid and accurate detection of CPO is crucial to a targeted infection control strategy, as in Tan Tock Seng Hospital (TTSH), a large tertiary hospital in Singapore, where cohorting of CPO colonised patients is driven by PCR-based genotypic identification. A newly released panel for the BD Phoenix system, the CPO Detect panel, includes CPO detection with Amber Class identification, alongside standard Phoenix antibiotic susceptibility testing. We evaluated this system in the context of the TTSH CPO control strategy. Methods: A total of 201 isolates from CHROMID ® positive rectal swabs taken as part of inpatient screening, and from clinical samples with confirmed carbapenem resistance, were assayed prospectively between January and April 2018. Ninety-five samples were sampled retrospectively from 2017. CPO genotype was determined using PCR targeting NDM, KPC, oxa48-like, IMI and IMP carbapenemases. Isolates were analysed on the CPO Detect assay in parallel. Results: A broad range of CPO genotypes was achieved and results were comparable in both prospective and retrospective samples. Overall, a concordance of 76% was found between CPO Detect determination of CPO status (both positive and negative) and PCR (238/313 isolates). PCR genotype was in agreement with the Ambler class found by CPO Detect in 151/200 positives (75.5%), 27 samples were not assigned an Ambler class and Ambler class was mismatched in 8 samples. Partial agreement was noted in 17 samples in which CPO Detect indicated a single Ambler class, but PCR identified two carbapanemase genes. CPO Detect outright failed to detect 14/200 PCR positive samples (7%) of which 10 were IMI. CPO Detect did however identify a CPO in a further 54 samples which were PCR negative. Conclusion: Compared with PCR, CPO Detect had a sensitivity of 93% in CPO detection and agreement of 75.5% with respect to Ambler class specificity. False negatives were overwhelmingly the IMI genotype. We are continuing to characterise these by further molecular means, as well as the 54 samples found by CPO Detect but PCR negative. Disclosures: All authors: No reported disclosures.